Уменьшение влияния пиротехнических зарядов на работу измерительных усилителей - Startsev, V. I.; Yampolsky, Ju. S.; Kutsenko, A. P. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
The article observes sсhemotehnic methods of influence reduction of piroelektric effect on charge-sensitive amplifiers functioning. The taken action allows to essentially reduce the influence of piroelektric currents caused by temperature change on the level of output tension of charge-sensitive amplifiers.